The evaluation of sewage sludge application as a fertilizer for broad bean (Faba sativa Bernh.) crops. (2nd August 2018) - Eid, Ebrahem M.; Alrumman, Sulaiman A.; El‐Bebany, Ahmed F.; Fawy, Khaled F.; Taher, Mostafa A.; Hesham, Abd El‐Latif; El‐Shaboury, Gamal A.; Ahmed, Mohamed T.
Abstract: Although several studies have examined the effect of sewage sludge (SS) application on various legume crops, there is insufficient information confirming the agronomic and environmental sustainability of SS usage in a broad bean cultivation systems. Therefore, a greenhouse experiment was completed to assess the soil heavy metal (HM) pools, growth, yield, and HM uptake of Faba sativa Bernh. (broad bean) grown in the agricultural soils supplemented with SS in comparison to control soils (nonamended). The experimental design was completely randomized with six replicates. The amendment with SS significantly elevated the organic matter (OM) content, soil salinity and Al, Co, Cr, Cu, Fe, Mn, Ni, Pb, and Zn concentrations, although the soil pH decreased. As allowed by the Council of European Communities, the concentrations of the determined HMs were less than the accepted limit for SS used in agriculture. Generally, SS applications of up to 120 t/ha produced a considerable increase in the growth measurements and biomass of broad bean. However, the broad bean biomass, shoot height, number of branches, root length, absolute growth rate, number of leaves, and leaf area declined in reaction to a rate of 150 t/ha. The HM concentrations in various tissues of broad bean plants exposed to SS were significantly higher than those in the untreated plants. However, most HM concentrations were inside the permissible limits and did not overcome the maximum levels of phytotoxic. The broad bean was recognized by a bioaccumulation factor less than 1.0 for the majority of the HMs. The translocation factors for the determined HMs (excluding for Al, Co, and Pb in stems and leaves) were less than 1.0. Therefore, the SS utilized in this study could be used as a fertilizer for broad bean crops and could as well act as a replacement manner for SS elimination. Abstract : A greenhouse experiment was performed to assess the soil heavy metal pools, growth, yield, and heavy metal uptake of Faba sativa Bernh. (broad bean) grown in the agricultural soils supplemented with sewage sludge (SS) in comparison to control soils (nonamended).